Rare earth modified cast steel material for high-speed rail brake disc and preparation method of rare earth modified cast steel material

By using porous carbon microspheres loaded with lanthanum and scandium in high-speed rail brake disc materials, the lack of performance of traditional cast steel materials under high-temperature conditions is solved, and the high strength, toughness and wear resistance of the material are achieved.

CN119913435AActive Publication Date: 2025-05-02WENSHANG HAIWEI MOTORCYCLE ACCESSORIES CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510111487.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-05-02
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

Traditional cast steel materials have fluctuated friction coefficient, increased wear and insufficient oxidation resistance under high temperature conditions, making it difficult to meet the strict working conditions of high-speed rail brake discs.

Method used

Rare earth modified cast steel materials are used to uniformly distribute porous carbon microspheres loaded by lanthanum and scandium in the steel matrix, optimizing the grain structure and microstructure of the material to form a stable oxide film.

Benefits of technology

It significantly improves the tensile strength, impact toughness, high-temperature friction resistance and oxidation resistance of the material, and can maintain stable performance during high-speed operation and frequent braking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005256749510000101
    Figure BDA0005256749510000101
  • Figure BDA0005256749510000112
    Figure BDA0005256749510000112
Patent Text Reader

Abstract

The invention relates to the technical field of metal materials, in particular to a rare earth modified cast steel material for a high-speed rail brake disc and a preparation method of the rare earth modified cast steel material. The rare earth modified cast steel material comprises carbon, manganese, aluminum, nickel, chromium, molybdenum, titanium, vanadium, lanthanum, scandium and other elements, rare earth elements lanthanum and scandium are introduced by being loaded on porous carbon microspheres, and the porous carbon microspheres have large specific surface areas and rich pore structures, so that the rare earth elements are distributed more uniformly, grains are further refined, the microstructure is optimized, and the rare earth elements are further refined. Therefore, the tensile strength, the impact toughness and the high-temperature friction resistance of the material are remarkably improved. The prepared rare earth modified cast steel material meets the requirements for high strength, high toughness and high-temperature stability of the high-speed rail brake disc, and has important application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal materials, and in particular to a rare earth modified cast steel material for a high-speed railway brake disc and a preparation method thereof. Background Art

[0002] High-speed rail brake discs are key components in the braking system of high-speed trains, and their performance is directly related to the safety and reliability of train operation. During high-speed operation and frequent braking, brake discs need to withstand high stress, impact loads, and high-temperature friction environments, which places extremely high demands on the mechanical properties and high-temperature friction resistance of their materials. Although traditional cast steel materials have certain strength and toughness, they are prone to friction coefficient fluctuations, increased wear, and insufficient antioxidant properties under high temperature conditions, making it difficult to meet the harsh working conditions of high-speed rail brake discs.

[0003] In recent years, rare earth elements have been widely used in the modification research of steel materials due to their unique modification and strengthening effects. Rare earth elements lanthanum and scandium can refine grains, optimize microstructures, and form stable oxide films under high temperature conditions, thereby significantly improving the strength, toughness and high temperature friction resistance of the material. However, the uniformity of the distribution of rare earth elements in the steel matrix has an important influence on its modification effect. The traditional method of adding rare earth elements has the problems of uneven distribution and low utilization rate, which limits the further improvement of its performance.

[0004] In summary, the development of a rare earth modified cast steel material and its preparation method can significantly improve the mechanical properties and high temperature friction resistance of high-speed rail brake disc materials, which has important engineering application value and promotion prospects. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a rare earth modified cast steel material for high-speed railway brake discs and a preparation method thereof, so as to solve the problems of uneven distribution and low utilization rate of traditional rare earth element addition methods.

[0006] Based on the above purpose, the present invention provides a rare earth modified cast steel material for high-speed railway brake disc, which includes the following chemical composition raw materials by weight percentage: carbon 0.64%-0.85%, manganese 14.2%-16.8%, aluminum 7.1%-8.2%, nickel 4.5%-5.6%, chromium 0.49%-0.58%, molybdenum 0.51%-0.59%, titanium 0.045%-0.055%, vanadium 0.035%-0.045%, lanthanum 0.005%-0.007%, scandium 0.001%-0.003%, sulfur ≤0.01%, phosphorus ≤0.01%, and the rest are iron and unavoidable impurities.

[0007] Furthermore, the carbon component, lanthanum component and scandium component are provided by porous carbon microspheres loaded with lanthanum and scandium.

[0008] Preferably, the lanthanum content in the lanthanum and scandium loaded porous carbon microspheres is 0.78wt%-0.82wt%, and the scandium content is 0.16wt%-0.35wt%.

[0009] Furthermore, the preparation steps of the lanthanum and scandium loaded porous carbon microspheres are as follows:

[0010] S1: Grind and mix chitosan and ammonium chloride, and then calcine in Ar gas at a temperature of 750-850°C for 2.5-3.5 hours, and cool to room temperature to obtain porous carbon microspheres;

[0011] S2: The porous carbon microspheres were immersed in a mixed aqueous solution of lanthanum nitrate and scandium nitrate for 8-12 hours, then washed and heated in an Ar / H 2 Calcination in the mixed gas at a temperature of 650-750°C, keeping the temperature for 1.5-2.5 hours, and cooling to room temperature to obtain porous carbon microspheres loaded with lanthanum and scandium;

[0012] Preferably, the weight ratio of chitosan to ammonium chloride in step S1 is 10:5-15.

[0013] More preferably, the rare earth modified cast steel material for high-speed rail brake disc includes the following chemical components: 0.72% carbon, 15.3% manganese, 7.7% aluminum, 5.1% nickel, 0.53% chromium, 0.56% molybdenum, 0.050% titanium, 0.032% vanadium, 0.006% lanthanum, 0.002% scandium, ≤0.008% sulfur, ≤0.005% phosphorus, and the rest is iron and unavoidable impurities.

[0014] Preferably, in step S2, Ar / H 2 The volume ratio of the mixed gas is 10:1.

[0015] Preferably, in step S2, the concentration of lanthanum nitrate is 17.8-19.1 g / L, and the concentration of scandium nitrate is 7.5-16.5 g / L.

[0016] Furthermore, the present invention also provides a method for preparing a rare earth modified cast steel material for a high-speed railway brake disc, comprising the following steps:

[0017] (1) Ingredients: Pure iron, electrolytic manganese, aluminum particles, nickel plates, metallic chromium, ferromolybdenum, titanium sponge, ferrovanadium, lanthanum and scandium loaded porous carbon microspheres are weighed separately according to the chemical composition raw material ratio;

[0018] (2) Melting: pure iron is added to a vacuum melting furnace, the vacuum degree is 0.3-0.6Pa, the temperature is raised to 1450-1550°C, lanthanum and scandium loaded porous carbon microspheres are added, Ar gas is passed to 800-1200Pa, electrolytic manganese, aluminum particles, nickel plates, metal chromium, ferromolybdenum, sponge titanium and ferrovanadium are added, the temperature is raised to 1630-1680°C, refined for 15-20min, deoxidized and degassed to obtain molten steel;

[0019] (3) Pouring: pouring molten steel into a sand mold and air-cooling it to room temperature to obtain a casting;

[0020] (4) Heat treatment: The casting is quenched and tempered to obtain rare earth modified cast steel material for high-speed railway brake disc.

[0021] Preferably, in step (4), the quenching is performed by heating the temperature to 900-1100°C at a heating rate of 40-60°C / min, keeping the temperature for 0.5-1.5h, and then quenching with oil to room temperature.

[0022] Preferably, in step (4), the tempering is performed at a heating rate of 40-60°C / min, the temperature is raised to 600-700°C, the temperature is kept for 0.5-1.5h, and then air-cooled to room temperature.

[0023] Beneficial effects of the present invention:

[0024] The rare earth modified cast steel material for high-speed rail brake discs provided by the present invention has high tensile strength and impact toughness, can withstand high stress and impact loads during high-speed operation and frequent braking, and meets the strict requirements of high-speed rail brake discs for strength and toughness. This is due to the addition of rare earth elements lanthanum and scandium, which optimizes the grain structure of the material and refines the grains, thereby significantly improving the strength and toughness of the material.

[0025] Rare earth modified cast steel materials for high-speed rail brake discs show excellent wear resistance and high temperature stability under high temperature conditions. The addition of rare earth elements lanthanum and scandium optimizes the microstructure of the material and forms a stable oxide film at high temperatures, reducing friction and wear while improving oxidation resistance, enabling the material to maintain stable performance under high temperature and complex working conditions.

[0026] The present invention uses porous carbon microspheres to load rare earth elements lanthanum and scandium, thereby making the rare earth metal particle size smaller and the distribution more uniform, further refining the grains, and optimizing the microstructure of the material, thereby significantly improving the mechanical properties and high temperature friction resistance of the material.

[0027] The porous carbon microspheres provided by the present invention have a large specific surface area and a rich pore structure, can load rare earth elements more evenly, and play a role of solid solution strengthening and grain boundary strengthening in the steel matrix as a reinforcing phase. The synergistic effect of the carbon microspheres and the rare earth elements effectively improves the grain boundary characteristics of the material, reduces grain boundary defects, and further improves the strength and wear resistance of the material.

[0028] The pressurization process during the smelting process of the present invention enables the molten steel to fully enter the pores of the porous carbon microspheres, significantly increases the contact area between the molten steel and the porous carbon microspheres, enables the rare earth elements to be more evenly dispersed in the steel matrix, and further enhances the solid solution strengthening and grain boundary strengthening effects of the porous carbon microspheres, thereby comprehensively improving the comprehensive performance of the material. DETAILED DESCRIPTION

[0029] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0030] Embodiment 1:

[0031] (1) Chitosan and ammonium chloride were ground and mixed in a weight ratio of 2:1, and then calcined in Ar gas at a calcination temperature of 750°C for 2.5 hours, and then cooled to room temperature to obtain porous carbon microspheres;

[0032] (2) The porous carbon microspheres were immersed in a mixed aqueous solution of lanthanum nitrate and scandium nitrate (the concentration of lanthanum nitrate was 17.8 g / L and the concentration of scandium nitrate was 7.5 g / L) for 8 h, then washed and heated in an Ar / H 2 The mixture was calcined in a mixed gas (volume ratio of 10:1) at a calcination temperature of 650°C, kept at this temperature for 1.5 hours, and then cooled to room temperature to obtain porous carbon microspheres loaded with lanthanum and scandium with a lanthanum content of 0.78wt% and a scandium content of 0.16wt%;

[0033] (3) Ingredients: Pure iron, electrolytic manganese, aluminum particles, nickel plates, metallic chromium, ferromolybdenum, titanium sponge, ferrovanadium, lanthanum and scandium loaded porous carbon microspheres were weighed according to the raw material ratio of chemical composition in Table 1;

[0034] (4) Melting: pure iron is added to a vacuum melting furnace, the vacuum degree is 0.3Pa, the temperature is raised to 1450°C, lanthanum and scandium loaded porous carbon microspheres are added, Ar gas is passed to 800Pa, electrolytic manganese, aluminum particles, nickel plates, metal chromium, ferromolybdenum, sponge titanium and ferrovanadium are added, the temperature is raised to 1630°C, refined for 15min, deoxidized and degassed to obtain molten steel;

[0035] (5) Pouring: pouring molten steel into a sand mold and air-cooling it to room temperature to obtain a casting;

[0036] (6) Heat treatment: The casting is quenched and tempered. The quenching temperature is raised to 900°C at a heating rate of 40°C / min, and the casting is kept at this temperature for 0.5h before oil quenching to room temperature. The tempering temperature is raised to 600°C at a heating rate of 40°C / min, and the casting is kept at this temperature for 0.5h before air cooling to room temperature to obtain a rare earth modified cast steel material for high-speed rail brake discs.

[0037] Embodiment 2:

[0038] (1) Chitosan and ammonium chloride were ground and mixed in a weight ratio of 1:1, and then calcined in Ar gas at a calcination temperature of 800°C for 3 hours, and then cooled to room temperature to obtain porous carbon microspheres;

[0039] (2) The porous carbon microspheres were immersed in a mixed aqueous solution of lanthanum nitrate and scandium nitrate (the concentration of lanthanum nitrate was 18.4 g / L and the concentration of scandium nitrate was 12 g / L) for 10 h, then washed and heated in an Ar / H 2 The mixture was calcined in a mixed gas (volume ratio of 10:1) at a calcination temperature of 700°C, kept at this temperature for 2 hours, and then cooled to room temperature to obtain porous carbon microspheres loaded with lanthanum and scandium with a lanthanum content of 0.79wt% and a scandium content of 0.26wt%;

[0040] (3) Ingredients: Pure iron, electrolytic manganese, aluminum particles, nickel plates, metallic chromium, ferromolybdenum, titanium sponge, ferrovanadium, lanthanum and scandium loaded porous carbon microspheres were weighed according to the raw material ratio of chemical composition in Table 1;

[0041] (4) Melting: pure iron is added into a vacuum melting furnace, the vacuum degree is 0.5Pa, the temperature is raised to 1500°C, lanthanum and scandium loaded porous carbon microspheres are added, Ar gas is passed to 1000Pa, electrolytic manganese, aluminum particles, nickel plates, metal chromium, ferromolybdenum, sponge titanium and ferrovanadium are added, the temperature is raised to 1660°C, refined for 18min, deoxidized and degassed to obtain molten steel;

[0042] (5) Pouring: pouring molten steel into a sand mold and air-cooling it to room temperature to obtain a casting;

[0043] (6) Heat treatment: The casting is quenched and tempered. The quenching temperature is raised to 1000°C at a heating rate of 50°C / min, and the casting is kept at this temperature for 1 hour before oil quenching to room temperature. The tempering temperature is raised to 650°C at a heating rate of 50°C / min, and the casting is kept at this temperature for 1 hour before air cooling to room temperature to obtain a rare earth modified cast steel material for high-speed rail brake discs.

[0044] Embodiment 3:

[0045] (1) Chitosan and ammonium chloride were ground and mixed in a weight ratio of 2:3, and then calcined in Ar gas at a calcination temperature of 850°C for 3.5 hours, and then cooled to room temperature to obtain porous carbon microspheres;

[0046] (2) The porous carbon microspheres were immersed in a mixed aqueous solution of lanthanum nitrate and scandium nitrate (the concentration of lanthanum nitrate was 19.1 g / L and the concentration of scandium nitrate was 16.5 g / L) for 12 h, then washed and heated in an Ar / H 2 The mixture was calcined in a mixed gas (volume ratio of 10:1) at a calcination temperature of 750°C, kept at this temperature for 2.5 hours, and then cooled to room temperature to obtain porous carbon microspheres loaded with lanthanum and scandium with a lanthanum content of 0.82wt% and a scandium content of 0.35wt%;

[0047] (3) Ingredients: Pure iron, electrolytic manganese, aluminum particles, nickel plates, metallic chromium, ferromolybdenum, titanium sponge, ferrovanadium, lanthanum and scandium loaded porous carbon microspheres were weighed according to the raw material ratio of chemical composition in Table 1;

[0048] (4) Melting: pure iron is added into a vacuum melting furnace, the vacuum degree is 0.6Pa, the temperature is raised to 1550°C, lanthanum and scandium loaded porous carbon microspheres are added, Ar gas is passed to 1200Pa, electrolytic manganese, aluminum particles, nickel plates, metal chromium, ferromolybdenum, sponge titanium and ferrovanadium are added, the temperature is raised to 1680°C, refined for 20min, deoxidized and degassed to obtain molten steel;

[0049] (5) Pouring: pouring molten steel into a sand mold and air-cooling it to room temperature to obtain a casting;

[0050] (6) Heat treatment: The casting is quenched and tempered. The quenching temperature is raised to 1100°C at a heating rate of 60°C / min, and the casting is kept at this temperature for 1.5 hours before oil quenching to room temperature. The tempering temperature is raised to 700°C at a heating rate of 60°C / min, and the casting is kept at this temperature for 1.5 hours before air cooling to room temperature to obtain a rare earth modified cast steel material for high-speed rail brake discs.

[0051] Comparative Example 1:

[0052] The difference between Comparative Example 1 and Example 2 is that: no lanthanum is loaded on the porous carbon microspheres, and lanthanum is introduced through lanthanum-iron alloy;

[0053] The specific steps are as follows:

[0054] (1) Chitosan and ammonium chloride were ground and mixed in a weight ratio of 1:1, and then calcined in Ar gas at a calcination temperature of 800°C for 3 hours, and then cooled to room temperature to obtain porous carbon microspheres;

[0055] (2) The porous carbon microspheres were immersed in a scandium nitrate aqueous solution (the concentration of scandium nitrate was 12 g / L) for 10 h, then washed and heated in an Ar / H 2 The mixture was calcined in a mixed gas (volume ratio of 10:1) at a calcination temperature of 700°C for 2 hours, and then cooled to room temperature to obtain porous carbon microspheres loaded with scandium having a scandium content of 0.28 wt%;

[0056] (3) Ingredients: Pure iron, electrolytic manganese, aluminum particles, nickel plates, metallic chromium, ferromolybdenum, titanium sponge, ferrovanadium, ferrolanthanum, and scandium-loaded porous carbon microspheres were weighed according to the chemical composition raw material ratios in Table 1;

[0057] (4) Melting: pure iron is added into a vacuum melting furnace, the vacuum degree is 0.5Pa, the temperature is raised to 1500°C, the scandium-loaded porous carbon microspheres are added, Ar gas is passed to 1000Pa, electrolytic manganese, aluminum particles, nickel plates, metal chromium, molybdenum iron, titanium sponge, vanadium iron and lanthanum iron are added, the temperature is raised to 1660°C, refined for 18 minutes, deoxidized and degassed to obtain molten steel;

[0058] (5) Pouring: pouring molten steel into a sand mold and air-cooling it to room temperature to obtain a casting;

[0059] (6) Heat treatment: The casting was quenched and tempered. The quenching temperature was raised to 1000°C at a heating rate of 50°C / min, kept at this temperature for 1 hour, and then oil quenched to room temperature. The tempering temperature was raised to 650°C at a heating rate of 50°C / min, kept at this temperature for 1 hour, and then air-cooled to room temperature to obtain a cast steel material.

[0060] Comparative Example 2:

[0061] The difference between Comparative Example 2 and Example 2 is that scandium is not loaded on the porous carbon microspheres, and scandium is introduced through a scandium-iron alloy;

[0062] The specific steps are as follows:

[0063] (1) Chitosan and ammonium chloride were ground and mixed in a weight ratio of 1:1, and then calcined in Ar gas at a calcination temperature of 800°C for 3 hours, and then cooled to room temperature to obtain porous carbon microspheres;

[0064] (2) The porous carbon microspheres were immersed in a lanthanum nitrate aqueous solution (the concentration of lanthanum nitrate was 18.4 g / L) for 10 h, then washed and heated in an Ar / H 2 The mixture was calcined in a mixed gas (volume ratio of 10:1) at a calcination temperature of 700°C, kept at this temperature for 2 hours, and then cooled to room temperature to obtain lanthanum-loaded porous carbon microspheres with a lanthanum content of 0.82 wt%;

[0065] (3) Ingredients: Pure iron, electrolytic manganese, aluminum particles, nickel plates, metallic chromium, ferromolybdenum, titanium sponge, ferrovanadium, ferroscdium, and lanthanum-loaded porous carbon microspheres were weighed according to the chemical composition raw material ratios in Table 1;

[0066] (4) Melting: pure iron is added to a vacuum melting furnace, the vacuum degree is 0.5Pa, the temperature is raised to 1500°C, lanthanum-loaded porous carbon microspheres are added, Ar gas is passed to 1000Pa, electrolytic manganese, aluminum particles, nickel plates, metal chromium, molybdenum iron, titanium sponge, vanadium iron, and scandium iron are added, and the temperature is raised to 1660°C, refined for 18 minutes, deoxidized and degassed, and molten steel is obtained;

[0067] (5) Pouring: pouring molten steel into a sand mold and air-cooling it to room temperature to obtain a casting;

[0068] (6) Heat treatment: The casting was quenched and tempered. The quenching temperature was raised to 1000°C at a heating rate of 50°C / min, kept at this temperature for 1 hour, and then oil quenched to room temperature. The tempering temperature was raised to 650°C at a heating rate of 50°C / min, kept at this temperature for 1 hour, and then air-cooled to room temperature to obtain a cast steel material.

[0069] Comparative Example 3:

[0070] The difference between Comparative Example 3 and Example 2 is that: lanthanum and scandium are not loaded on the porous carbon microspheres, and lanthanum and scandium are introduced through lanthanum-iron alloy and scandium-iron alloy respectively;

[0071] The specific steps are as follows:

[0072] (1) Chitosan and ammonium chloride were ground and mixed in a weight ratio of 1:1, and then calcined in Ar gas at a calcination temperature of 800°C for 3 hours, and then cooled to room temperature to obtain porous carbon microspheres;

[0073] (2) Ingredients: Pure iron, electrolytic manganese, aluminum particles, nickel plate, metallic chromium, ferromolybdenum, sponge titanium, ferrovanadium, ferrolanthanum, ferroscdium, and porous carbon microspheres were weighed according to the chemical composition raw material ratios in Table 1;

[0074] (3) Melting: pure iron is added to a vacuum melting furnace, the vacuum degree is 0.5Pa, the temperature is raised to 1500℃, porous carbon microspheres are added, Ar gas is passed to 1000Pa, electrolytic manganese, aluminum particles, nickel plates, metal chromium, molybdenum iron, sponge titanium, vanadium iron, lanthanum iron, scandium iron are added, and the temperature is raised to 1660℃, refined for 18min, deoxidized and degassed to obtain molten steel;

[0075] (4) Pouring: pouring molten steel into a sand mold and air-cooling it to room temperature to obtain a casting;

[0076] (5) Heat treatment: The casting was quenched and tempered. The quenching temperature was raised to 1000°C at a heating rate of 50°C / min, kept at this temperature for 1 hour, and then oil quenched to room temperature. The tempering temperature was raised to 650°C at a heating rate of 50°C / min, kept at this temperature for 1 hour, and then air-cooled to room temperature to obtain a cast steel material.

[0077] Comparative Example 4:

[0078] Comparative Example 4 is different from Example 2 in that the porous carbon microspheres loaded with lanthanum and scandium are replaced with graphite, and scandium and lanthanum-scandium are introduced through lanthanum-iron alloy and scandium-iron alloy, respectively;

[0079] The specific steps are as follows:

[0080] (1) Ingredients: Pure iron, electrolytic manganese, aluminum particles, nickel plate, metallic chromium, ferromolybdenum, sponge titanium, ferrovanadium, ferrolanthanum, ferro-scandium, and graphite are weighed according to the chemical composition raw material ratios in Table 1;

[0081] (2) Melting: pure iron is added into a vacuum melting furnace, the vacuum degree is 0.5Pa, the temperature is raised to 1500℃, graphite is added, Ar gas is passed to 1000Pa, electrolytic manganese, aluminum particles, nickel plate, metal chromium, molybdenum iron, sponge titanium, vanadium iron, lanthanum iron, scandium iron are added, and the temperature is raised to 1660℃, refined for 18min, deoxidized and degassed to obtain molten steel;

[0082] (3) Pouring: pouring molten steel into a sand mold and air-cooling it to room temperature to obtain a casting;

[0083] (4) Heat treatment: The casting is quenched and tempered. The quenching temperature is raised to 1000°C at a heating rate of 50°C / min, kept at this temperature for 1 hour, and then oil quenched to room temperature. The tempering temperature is raised to 650°C at a heating rate of 50°C / min, kept at this temperature for 1 hour, and then air-cooled to room temperature to obtain a cast steel material.

[0084] Comparative Example 5:

[0085] The difference between Comparative Example 5 and Example 2 is that: in step (4), Ar gas is not passed to 1000 Pa, but electrolytic manganese, aluminum particles, nickel plate, metallic chromium, ferromolybdenum, sponge titanium and ferrovanadium are directly added;

[0086] The specific steps are as follows:

[0087] (1) Chitosan and ammonium chloride were ground and mixed in a weight ratio of 1:1, and then calcined in Ar gas at a calcination temperature of 800°C for 3 hours, and then cooled to room temperature to obtain porous carbon microspheres;

[0088] (2) The porous carbon microspheres were immersed in a mixed aqueous solution of lanthanum nitrate and scandium nitrate (the concentration of lanthanum nitrate was 18.4 g / L and the concentration of scandium nitrate was 12 g / L) for 10 h, then washed and heated in an Ar / H 2 The mixture was calcined in a mixed gas (volume ratio of 10:1) at a calcination temperature of 700°C, kept at this temperature for 2 hours, and then cooled to room temperature to obtain porous carbon microspheres loaded with lanthanum and scandium with a lanthanum content of 0.79wt% and a scandium content of 0.26wt%;

[0089] (3) Ingredients: Pure iron, electrolytic manganese, aluminum particles, nickel plates, metallic chromium, ferromolybdenum, titanium sponge, ferrovanadium, lanthanum and scandium loaded porous carbon microspheres were weighed according to the raw material ratio of chemical composition in Table 1;

[0090] (4) Melting: pure iron is added into a vacuum melting furnace, the vacuum degree is 0.5 Pa, the temperature is raised to 1500°C, lanthanum and scandium loaded porous carbon microspheres, electrolytic manganese, aluminum particles, nickel plates, metal chromium, ferromolybdenum, sponge titanium and ferrovanadium are added, and the temperature is raised to 1660°C, refined for 18 minutes, deoxidized and degassed to obtain molten steel;

[0091] (5) Pouring: pouring molten steel into a sand mold and air-cooling it to room temperature to obtain a casting;

[0092] (6) Heat treatment: The casting was quenched and tempered. The quenching temperature was raised to 1000°C at a heating rate of 50°C / min, kept at this temperature for 1 hour, and then oil quenched to room temperature. The tempering temperature was raised to 650°C at a heating rate of 50°C / min, kept at this temperature for 1 hour, and then air-cooled to room temperature to obtain a cast steel material.

[0093] Table 1 Chemical composition of the embodiments and comparative examples by weight percentage

[0094]

[0095]

[0096] Performance Test:

[0097] Tensile test: The tensile test was carried out on a universal testing machine in accordance with the national standard GB / T228.1-2010, with a tensile rate of 1.5 mm / min and an inlet force of 300 N. The results are shown in Table 2.

[0098] Impact test: V-notch specimens were used, with the notch of the impact specimen facing the direction of the pendulum. The pendulum energy was 300 J. Three impact tests were performed on each group of specimens, and the average value was taken. The results are shown in Table 2.

[0099] High temperature friction and wear: The high temperature friction and wear test was carried out using a high-speed high temperature friction and wear testing machine. According to the equipment standard, the test temperature was 400±5℃, the rotation speed was 1850rpm, and the braking load was 1.8MPa. The friction coefficient and wear amount were measured. Three samples were tested in each group and the average value was taken. The results are shown in Table 2.

[0100] Table 2 Performance test results

[0101]

[0102] Data Analysis:

[0103] It can be seen from the data of Examples 1-3 in Table 2 that the rare earth modified cast steel material for high-speed rail brake discs prepared by the present invention has high tensile strength and impact toughness, which indicates that the material has excellent mechanical properties when subjected to high stress and impact loads, and can meet the strict requirements of high-speed rail brake discs on strength and toughness during high-speed operation and frequent braking. This is because the addition of rare earth elements lanthanum and scandium optimizes the grain structure of the material, refines the grains, and improves the strength and toughness of the material.

[0104] From the data of Examples 1-3 in Table 2, it can be seen that the rare earth modified cast steel material for high-speed rail brake disc prepared by the present invention has excellent high temperature friction resistance, which indicates that the material can exhibit excellent wear resistance and high temperature stability under high temperature conditions. This is because the addition of rare earth elements lanthanum and scandium optimizes the microstructure of the material and forms a stable oxide film at high temperature, reducing friction and wear, while improving oxidation resistance. Ordinary technicians in the field should understand.

[0105] It can be seen from the data of Example 2 and Comparative Examples 1-3 in Table 2 that the method of adding lanthanum and scandium has a great influence on the mechanical properties and high-temperature friction resistance of the cast steel material. The introduction of lanthanum and scandium by loading lanthanum and scandium on porous carbon microspheres can significantly improve the mechanical properties and high-temperature friction resistance of the cast steel material. This is mainly because the lanthanum and scandium loaded on the porous carbon microspheres have a smaller particle size. When the molten steel is immersed into the pores, the rare earth elements can be evenly distributed and the grains can be refined, optimizing the microstructure of the material, thereby improving the mechanical properties and high-temperature friction resistance.

[0106] It can be seen from the data of Example 2 and Comparative Examples 3-4 in Table 2 that, relative to graphite, porous carbon microspheres can further improve the tensile strength and high-temperature friction resistance of cast steel materials. This is mainly because, on the one hand, porous carbon microspheres have a large specific surface area and rich pore structure, which can more evenly load the rare earth elements lanthanum and scandium, making them more evenly distributed in the molten steel; on the other hand, porous carbon microspheres, as a reinforcing phase, play a role of solid solution strengthening in the steel matrix, and their synergistic effect with rare earth elements can effectively improve the grain boundary characteristics of the material, reduce grain boundary defects, and improve the strength and wear resistance of the material.

[0107] It can be seen from the data of Example 2 and Comparative Example 5 in Table 2 that the pressurization process during the smelting process can further improve the mechanical properties and high-temperature friction resistance of the cast steel material. This may be because the pressurization process can prompt the molten steel to enter the pores of the porous carbon microspheres, thereby increasing the contact area between the molten steel and the porous carbon microspheres, so that the rare earth elements lanthanum and scandium can be more evenly dispersed in the steel matrix, and the porous carbon microspheres have a solid solution strengthening and grain boundary strengthening effect.

[0108] The discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples; within the context of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A rare earth modified cast steel material for high-speed railway brake disc, characterized in that: The raw materials include the following chemical components by weight percentage: carbon 0.64%-0.85%, manganese 14.2%-16.8%, aluminum 7.1%-8.2%, nickel 4.5%-5.6%, chromium 0.49%-0.58%, molybdenum 0.51%-0.59%, titanium 0.045%-0.055%, vanadium 0.035%-0.045%, lanthanum 0.005%-0.007%, scandium 0.001%-0.003%, sulfur ≤0.01%, phosphorus ≤0.01%, and the rest is iron and unavoidable impurities; The carbon component, lanthanum component and scandium component are provided by lanthanum and scandium loaded porous carbon microspheres; the lanthanum content of the lanthanum and scandium loaded porous carbon microspheres is 0.78wt%-0.82wt%, and the scandium content is 0.16wt%-0.35wt%; The preparation steps of the lanthanum and scandium loaded porous carbon microspheres are as follows: S1: Grind and mix chitosan and ammonium chloride, and then calcine in Ar gas at a temperature of 750-850°C for 2.5-3.5 hours, and cool to room temperature to obtain porous carbon microspheres; S2: The porous carbon microspheres are immersed in a mixed aqueous solution of lanthanum nitrate and scandium nitrate for 8-12 hours, then washed, calcined in an Ar / H2 mixed gas at a temperature of 650-750°C, kept warm for 1.5-2.5 hours, and cooled to room temperature to obtain lanthanum and scandium loaded porous carbon microspheres; In step S1, the weight ratio of chitosan to ammonium chloride is 10:5-15.

2. The rare earth modified cast steel material for high-speed railway brake disc according to claim 1, characterized in that: The rare earth modified cast steel material for high-speed rail brake disc includes the following chemical components: 0.72% carbon, 15.3% manganese, 7.7% aluminum, 5.1% nickel, 0.53% chromium, 0.56% molybdenum, 0.050% titanium, 0.032% vanadium, 0.006% lanthanum, 0.002% scandium, ≤0.008% sulfur, ≤0.005% phosphorus, and the rest is iron and unavoidable impurities.

3. The rare earth modified cast steel material for high-speed railway brake disc according to claim 1, characterized in that: The volume ratio of the Ar / H2 mixed gas in step S2 is 10:

1.

4. The rare earth modified cast steel material for high-speed railway brake disc according to claim 1, characterized in that: In step S2, the concentration of lanthanum nitrate is 17.8-19.1 g / L, and the concentration of scandium nitrate is 7.5-16.5 g / L.

5. A method for preparing the rare earth modified cast steel material for high-speed railway brake disc according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Ingredients: Pure iron, electrolytic manganese, aluminum particles, nickel plates, metallic chromium, ferromolybdenum, titanium sponge, ferrovanadium, lanthanum and scandium loaded porous carbon microspheres are weighed separately according to the chemical composition raw material ratio; (2) Melting: pure iron is added to a vacuum melting furnace, the vacuum degree is 0.3-0.6Pa, the temperature is raised to 1450-1550°C, lanthanum and scandium loaded porous carbon microspheres are added, Ar gas is passed to 800-1200Pa, electrolytic manganese, aluminum particles, nickel plates, metal chromium, ferromolybdenum, sponge titanium and ferrovanadium are added, the temperature is raised to 1630-1680°C, refined for 15-20min, deoxidized and degassed to obtain molten steel; (3) Pouring: pouring molten steel into a sand mold and air-cooling it to room temperature to obtain a casting; (4) Heat treatment: The casting is quenched and tempered to obtain rare earth modified cast steel material for high-speed railway brake disc.

6. The method for preparing the rare earth modified cast steel material for high-speed railway brake disc according to claim 5, characterized in that: In the step (4), the quenching is performed by heating the temperature to 900-1100° C. at a heating rate of 40-60° C. / min, keeping the temperature for 0.5-1.5 h, and then quenching with oil to room temperature.

7. The method for preparing the rare earth modified cast steel material for high-speed railway brake disc according to claim 5, characterized in that: In the step (4), the temperature is raised to 600-700°C at a heating rate of 40-60°C / min, kept at this temperature for 0.5-1.5h, and then air-cooled to room temperature.

Citation Information

Patent Citations

  • Rare earth multicomponent micro-alloying high-chromium cast iron and uses thereof

    CN101012526A

  • High carbon alloy steel wear-resistance valve material and preparation method thereof

    CN103695792A

  • Steel

    RU2026408C1